Political efficacy and participation An empirical analysis in European countries - Prats, Mariana (OECD Working Papers on Public Governance, 2021)
The active participation of citizens is the lifeblood of any functioning democracy. But what drives people's willingness to participate in political life? A key driver is their self-perception of their ability to understand political processes and to influence change through their action. These attitudes also determine people's level of trust in government, making it a cornerstone of research and work on trust. In a context of increasing concerns regarding democratic legitimacy and decreasing levels of political participation, this paper aims to analyse empirically to what extent people's attitudes towards their ability to influence and engage in political life - or their "political efficacy" - affect their political behaviour, including different forms of participation. A better understanding of political attitudes can help governments anticipate democratic deficits and develop strategies to improve political efficacy and promote participation